Grammatical and lexical errors of japanese sentence essay of stikes medistra Lubuk Pakam nurses as apprentices to Japan - Hasibuan, Adriana; Arfianty, Rani (Talenta Publisher, 2019)
This paper aims to analyze Japanese grammatical and lexical errors in written languages. This study involved 45 nurses from the School of Health Sciences as apprentices to Japan with a 180-word Japanese essay sample based on the Language error definition of Corder (1981) and Weinreich's interference definition (1970). In the process of switching Indonesian into Japanese, errors always occur as they speak. Language learners simply move the grammar rules of Indonesian language into Japanese without thinking about the rules that exist in Japanese. Translating from Indonesian into Japanese, interference is the most powerful factor. When learning Japanese, Indonesian as a mother tongue (B1) is always disruptive, Indonesian language has an influence on grammatical and lexical errors of Japanese written by STIKES nurse of Medistra Lubuk Pakam as apprentices to Japan. Errors made by nurses based on linguistic categories were 33.66% errors in the morphology field, 23.38% syntactic errors and 42.96% errors in the lexical field. Error occurred due to negative transfer.